If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5y + -4 = -19 Reorder the terms: -4 + -5y = -19 Solving -4 + -5y = -19 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -5y = -19 + 4 Combine like terms: -4 + 4 = 0 0 + -5y = -19 + 4 -5y = -19 + 4 Combine like terms: -19 + 4 = -15 -5y = -15 Divide each side by '-5'. y = 3 Simplifying y = 3
| 4x+42=46 | | 11n^2-8n+2=0 | | x+10-3=20 | | Sinx=.512477 | | -1.2x-0.8=-1.6x+3 | | 2A+9B-C+3D+5E+7F=138 | | -4(u-1)=-8u+20 | | A-2B+4C+6D+2E+4F=52 | | -3x+46=-2z+36 | | 2v/5-3wv=40w=10 | | A-B+C-D+E-F=-6 | | 2q+58=4q+50 | | 2s-35=131 | | 1.3h+3.7h=5 | | 50-7k=24 | | 0.8c+9=8(0.6c-2) | | 6(k+4)=3k-12 | | -2x=3x+3 | | 5z-96z+2z+4=12z-156 | | 4x+1=.15 | | 12b+3whenb=-4 | | 1/3=954/s | | 6c=3(c+4)-c | | 5z-96z+2z+4=2(6z-78) | | 1.8=0.03x-58.32 | | 4x+35x=21x+28 | | 2+4(x-7)=5-4(x-5) | | 8x+47=8(x+6) | | -1+3x=3+25x | | 5(3m-4)-8=-88 | | f(x)=x^3-28x+48 | | 6(2x+5)=2 |